Cell‐Free Multi‐Enzyme Synthesis and Purification of Uridine Diphosphate Galactose. (14th December 2021) - Mahour, Reza; Lee, Ju Weon; Grimpe, Pia; Boecker, Simon; Grote, Valerian; Klamt, Steffen; Seidel‐Morgenstern, Andreas; Rexer, Thomas F. T.; Reichl, Udo
Abstract: High costs and low availability of UDP‐galactose hampers the enzymatic synthesis of valuable oligosaccharides such as human milk oligosaccharides. Here, we report the development of a platform for the scalable, biocatalytic synthesis and purification of UDP‐galactose. UDP‐galactose was produced with a titer of 48 mM (27.2 g/L) in a small‐scale batch process (200 μL) within 24 h using 0.02 genzyme /gproduct . Through in‐situ ATP regeneration, the amount of ATP (0.6 mM) supplemented was around 240‐fold lower than the stoichiometric equivalent required to achieve the final product yield. Chromatographic purification using porous graphic carbon adsorbent yielded UDP‐galactose with a purity of 92 %. The synthesis was transferred to 1 L preparative scale production in a stirred tank bioreactor. To further reduce the synthesis costs here, the supernatant of cell lysates was used bypassing expensive purification of enzymes. Here, 23.4 g/L UDP‐galactose were produced within 23 h with a synthesis yield of 71 % and a biocatalyst load of 0.05 gtotal_protein /gproduct . The costs for substrates per gram of UDP‐galactose synthesized were around 0.26 €/g. Abstract : An enzymatic platform was developed for the synthesis of UDP‐Gal from low‐cost and readily available precursors. The overall process was optimized for efficiency by bypassing time‐consuming and expensive enzyme purification steps followed by a scale‐up into a 1 L bioreactor. Here, within 23 h, a total of 23.4 g/L of UDP‐galactose were produced. Costs for substrates per gram of UDP‐Gal synthesized were 0.26 €/g.